Investigation on the Presence of Income SmoothingaA Study on the Companies Listed in NSE (Global Journal of Management and Business Research, 2015)
In today's world information and economic systems, given to the development of information technology, transmission and accurate reporting of related financial information reliable on decision making has particular important. However, shareholders, who give their savings in the form of investment to companies, have not any tools except the annual financial statements, reports and notes of companies for knowing how to manage their assets and ensure the accuracy of performance, efficiency and productivity of managers. Government also due to different reasons like ensuring the accuracy of funds and sources consumption income analysis through tax and so on requires an accurate, reliable financial reporting. Government also due to different reasons like ensuring the accuracy of funds and sources consumption income analysis through tax and so on requires an accurate, reliable financial reporting.
Keywords: income smoothing; nse; earning management; financial reporting